Research on the Interactive Relationship between Government-industry-university-research Collaborative Innovation and Cultural Industry Personnel Training - Dong, Shu (Transactions on Social Science, Education and Humanities Research, 2023)
With the vigorous development of urban cultural industries, the need to promote the development of local economy and culture, and the deepening of mass entrepreneurship and innovation, there is an increasing demand for talents in cultural industry management, and more and more attention is paid to the talent training of students in cultural industry management in various schools. Taking the practical course of cultural Industry Management offered by Liaoning University of Communication as an example, this project focuses on how applied undergraduate colleges should carry out and optimize the practical teaching mode, organically combine the practical teaching mode with innovation and entrepreneurship education, and closely combine the training goal of applied talents with the training of students’ entrepreneurial consciousness and innovative spirit. Effectively enhance students’ ability of innovation and entrepreneurship, and cultivate innovative and compound cultural industry management talents.